Pengelolaan Hutan Berbasis Masyarakat (PHBM) Pada Hutan Lindung Gambut (HLG) di Desa Pematang Rahim Provinsi Jambi - Rahman, Fajri; Apriwan, Apriwan; Irwandi, Ade (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Sungai Buluh Peat Protection Forest is a peat area with protected forest status in Jambi Province. Protected forests are not only aimed at preservation, and protection but also open up utilization opportunities for local communities. The utilization is through Social Forestry (SF) which turns part of the forest area into a Village Forest. This aims to open up opportunities and access for local communities. A critical ethnographic approach explains the meaning behind the reality, where the forest is not only protected but has an economic impact on the surrounding community. Through interviews, observation and documentation techniques, data was collected. Informants consisted of KPHD, KUPS, community leaders, stakeholders, KKI Warsi and local communities to provide their views on the village forest scheme and how it impacts their lives. The results show that forestry provides opportunities for community-based forest management with the aim of protection, preservation and utilization. Through KPHD the village forest is managed and provides economic opportunities through KUPS which consists of the community in Pematang Rahim Village. Thus, through social forestry the forest can be maintained and local communities experience economic improvement. However, the challenge is that efforts to sustain forest protection and utilization must be supported by all sectors so that forest management by the community provides welfare and maximum protection efforts are achieved.